Women in agriculture and the implications for nutrition - Malapit, Hazel J. (International Food Policy Research Institute, 2019)
This chapter discusses the role of women in agriculture, and the ways in which their status affects the health and nutrition of their households. It highlights recent literature on the impacts of gendered and nutrition-sensitive agricultural programs. It also goes beyond a singular focus on women to consider the role of gender dynamics in agriculture and nutrition, and why the relationships between men and women are just as important for nutrition. Finally, it considers the ways in which agricultural research and nutrition-sensitive agricultural interventions can be designed so as to achieve better outcomes within nutrition and gender, and how these outcomes can be more accurately measured.